Comparative study of the dynamism of teeth eruption among children residing in an area with formerly fluorine-contaminated atmosphere - Zielińska, Ewa; Loster, Jolanta; Loster, Bartłomiej (Journal of Stomatology, 2015)
Aim of the study. Research was conducted in the 1970s among children living in a fluorine-contaminated area of the Polish town of Skawina. The results revealed slowing down of permanent tooth eruption. The aim of this research was to conduct a comparative study among children currently living the formerly fluorine-contaminated area in relation to children who lived in the same area during the period of fluorine contamination. Material and methods. Group I, the research group, consisted of 1190 children from Skawina. Group II, the control one, consisted of the 1201 Skawina children who were investigated in the 1970s’ research. Group III, the present-day control group, consisted of 511 subjects from Cracow. Each group was divided into one-year age subgroups ranging from 7 to 14 years. Results. The dynamism of permanent tooth eruption in the research group was greater than that of the group from the 1970s, but increased dynamism was not observed in all age groups. Significant differences were found in the 7-year-old, 9-year-old, and 12-year-old male subgroups and the 8-, 12-, and 13-year-old female subgroups, in the number of permanent teeth per individual. Conclusions. The dynamism of permanent tooth eruption in the research group of children living in the area previously contaminated with fluorine is greater than that of the children who lived there 40 years earlier during the period of pollution. There is some impact of the environment, but the process involves many factors and it is not possible to assess one factor in isolation from the other. Periodic verification of time and sequence of eruption for the population residing in a specific environment is indicated.